2013
DOI: 10.1007/s11010-013-1617-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damages in erythrocytes of patients with metabolic syndrome

Abstract: The aim of the study was to estimate the changes caused by oxidative stress in structure and function of membrane of erythrocytes from patients with metabolic syndrome (MS). The study involved 85 patients with MS before pharmacological treatment and 75 healthy volunteers as a control group. Cholesterol level, lipid peroxidation, glutathione level (GSH), and antioxidant enzyme activities in erythrocytes were investigated. The damage to erythrocyte proteins was also indicated by means of activity of ATPase (tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
3
20
2
3
Order By: Relevance
“…Although many studies reported a direct correlation between the membrane cholesterol and NKA activity,[12] some have observed an increased value of membrane cholesterol with decreased NKA activity, particularly in cases of metabolic syndrome. [13] Hence, significant lacunae still exist regarding the relationship between alterations in membrane cholesterol and NKA activity in different pathophysiological conditions including neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies reported a direct correlation between the membrane cholesterol and NKA activity,[12] some have observed an increased value of membrane cholesterol with decreased NKA activity, particularly in cases of metabolic syndrome. [13] Hence, significant lacunae still exist regarding the relationship between alterations in membrane cholesterol and NKA activity in different pathophysiological conditions including neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Specifically, peroxidation of membrane (phospho)lipids (PLs) can impair membrane functions, decrease fluidity, lead to inactivation of membrane-bound receptors and increase permeability to ions and even cause membrane rupture. [19] High levels of oxidative stress can even induce cell death directly by necrosis, while mild oxidative stress can trigger the process of apoptosis. [20] Lipid peroxidation occurs when ROS react with the lipid-esterified fatty acyl residues, particularly with polyunsaturated ones.…”
Section: Introductionmentioning
confidence: 99%
“…Ziobro et al observed that the concentration of thiol groups in erythrocyte membranes from patients with metabolic syndrome was significantly lower (about 16%) compared to the control group. The results were correlated with a substantially lower membrane fluidity (metabolic syndrome vs. control) [44]. The biochemical profile of the investigated patients indicated the increase in the CVD risk for HC patients compared to NC subjects.…”
Section: Discussionmentioning
confidence: 69%